Prevalência dos distúrbios nutricionais em crianças e adolescentes com Bronquiolite obliterante pós-infecciosa - Andrea Costa Morais Amaral (2012)
Objectives: review the literature on nutritional evaluation for general and specific nutritional aspects in post infectious bronchiolitis obliterans (BO) in children and adolescents. Data source: a non systematic review of the literature between 1990 and 2012 was carried out in the Medline/Pubmed, Lilacs and Ibecs, Biblioteca Cochrane and HighWare databases, based on the descriptors: bronchiolitis obliterans, child, adolescent, body mass index, body composition, nutritional status and nutritional evaluation (in Portuguese), all followed by their respective synonyms in English and Spanish. Due to their historical importance, classic articles on nutrition were included, such as those by Tanner (1962), Gomes (1946), Waterllow (1972), Ariza-Macias (1972), Marcondes (1982) and Frisancho (1990). The websites of the World Health Organization (WHO) and the Ministry of Health were also researched. Data synthesis: the evaluation of nutritional status is comprised of a complete medical history, including the background to the current disease, family history, food history, physical and laboratory exams and, in particular, anthropometric measures, evaluation of body composition and identification of puberty stages. The following are among the most used classifications: National Center for Health Statistics, from 1977 (NCHS/1977), Santo André (1982), Must et al. (1991), from the Centers for Disease Control and Prevention, 2000 (CDC/2000), Cole et al. (2002 and 2006) and Conde and Monteiro (2006). In 1995, WHO convened a multicentric group to create a new reference that could be used as an international standard, published in 2006 and 2007. In this review, it was possible to identify 232 patients through studies that used various nutrition classifications. Among these, we classified 37% as eutrophic (IC95%; 30.9-43.7) and 18.5% as malnourished (light and moderate), (IC95%; 13.9-24.3). 4.3% of the sample were overweight (IC95%; 2.2-8.0) and 5.6% were obese (IC95%; 3.1- 9.6). Only one study was aimed at specifically evaluating nutritional status in BO and it found 21.1% to be malnourished, 17.5% in risk of malnutrition, 42.1% eutrophic, 8.8% overweight and 10.5% obese. Conclusions: The diverse classifications hinder the evaluation of the prevalence of nutritional status, but the literature converges to highlight the importance of nutritional status evaluation and the need for more studies aimed at specifically evaluating the nutritional status of children and adolescents with post-infectious bronchiolitis obliterans.